Testing proximal, intermediate, and health outcomes of patient centered communication among non-pregnant women of childbearing age with diabetes mellitus: Findings from the Medical Expenditure Panel Survey 2012-2018 - Tiffany B. Kindratt; Godfred O. Boateng; Grace Ellen Brannon; Bala Yadu Vamsi Sankuratri; Kyrah K. Brown (Elsevier, 2023)
Objective: To determine associations between patient-centered communication (PCC) and overall healthcare ratings, self-efficacy, and management adherence among reproductive-age women with diabetes within the framework of Epstein and Street's conceptual model. Methods: We analyzed longitudinal data from the 2012-2018 Medical Expenditure Panel Survey. The sample included 493 non-pregnant women of childbearing age (18-45 years) with diabetes. Independent variables were domains of PCC (listening, explaining, respecting, spending time, giving instructions, among others). Dependent variables were overall healthcare ratings, self-efficacy, and management adherence. Crude and adjusted associations were evaluated. Results: Non-pregnant women of childbearing age who reported that their provider always listened to them, explained things, showed respect, and spent enough time with them had greater odds of reporting high overall healthcare ratings. Those who reported their provider always listened to them and spent enough time with them had greater odds of reporting better diabetes care adherence than those whose health care providers did not. Conclusion: Findings demonstrate that non-pregnant women of childbearing age who report having optimal PCC are more likely to adhere to their diabetes care regimen. Innovation: This is the first known study using a nationally representative sample of non-pregnant women of childbearing age to examine multiple layers of PCC.